Menyingkap Isyarat Profil Pancasila dalam Al-Qur’an dan Implikasinya Terhadap Pembentukan Karakter Siswa - Utomo, Edi; Rizal, Suaib; Risnawati, Risnawati; Rizqa, Miftahir (Fitrah: Journal of Islamic Education, 2023)
The threat of national disintegration is one of the factors in the need for a Pancasila student profile. This profile has been regulated in the Minister of Education and Culture regulation no. 22 of 2020 include: 1) having faith, piety and noble morals, 2) accepting diversity, 3) being able to work together or mutual cooperation, 4) being able to think critically, 5) being independent, and 6) having creativity. It turns out that the Al-Qur’an hints at this profile, so this study aims to analyze the profile of Pancasila students in the perspective of the Al-Qur’an and its implications for the formation of student character. The method applied in this study is a literature review and interpretation approach. Literature review is used to analyze the Pancasila profile as stated in government regulations. The interpretation approach is used to analyze the Qur'anic signs about the profile of Pancasila. The results of the study explain that the Pancasila profile cues are contained in surah Ali Imran verse 102, al-Qolan verse 4, Ali Imran 190-191, al-Maidah verse 2, al-Hujurat verse 13, ar-Ra'd verse 11. These Pancasila profile signals have implications for strengthening character, especially for Islamic educational institutions.